PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM GAMES TOURNAMENT TERHADAP SIKAP TOLERANSI SISWA PADA PELAJARAN PPKN PADA KELAS IV SDN 232 PALEMBANG - Dinda Viesta Rindiyani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of the Team Games Tournament cooperative learning model on students' tolerance attitudes in learning Pancasila and Citizenship Education (PPKn) for grade IV. The Team Games Tournament model is one of the cooperative learning approaches that emphasizes teamwork through competitive but still educational game and tournament activities. The research method used is a quasi-experimental with a pretest-posttest control group design. The subjects of the study consisted of grade IV students in an elementary school, who were divided into an experimental group and a control group. Data were collected through a multiple-choice test of tolerance attitudes and analyzed using statistical tests. The results showed that there was a significant increase in tolerance attitudes in the experimental class, with an average pretest score of 52.173 and at the time of the posttest getting an average score of 81.739 in students who took part in learning with the Team Games Tournament cooperative model compared to students who took part in general cooperative learning only getting an average pretest score of 59.80 and at the time of the posttest getting an average score of 74.20. Thus, the cooperative learning model of the Team Games Tournament type is effective in improving students' tolerance attitudes in PPKn subjects. This study recommends the application of the Team Games Tournament cooperative learning model as an alternative learning strategy that is fun and builds tolerance character from an early age.